Hydrographic Feature Variation Caused Pronounced Differences in Planktonic Ciliate Community in the Pacific Arctic Region in the Summer of 2016 and 2019 - Wang, Chaofeng; Yang, Mengyao; He, Yan; Xu, Zhiqiang; Zhao, Yuan; Zhang, Wuchang; Xiao, Tian (Frontiers in Microbiology, 2022)
Planktonic ciliates are an important component of microzooplankton, but there is limited understanding of their responses to changing environmental conditions in the Pacific Arctic Region. We investigated the variations of ciliate community structure and their relationships with environmental features in the Pacific Arctic Region in summer 2016 and 2019. The Pacific water was warmer and more saline in 2019 than in 2016. The abundance and biomass of total ciliate and aloricate ciliate were significantly higher in 2019 than those in 2016, while those of tintinnid were significantly lower. The dominant aloricate ciliate changed from large size-fraction (>30 um) in 2016 to small size-fraction (10-20 um) in 2019. More tintinnid species belonging to cosmopolitan genera were found in 2019 than in 2016, and distribution of tintinnid species (Codonellopsis frigida, Ptychocylis obtusa, and Salpingella sp.1) in 2019 expanded 5.9, 5.2 and 8.8 degrees further north of where they occurred in 2016. The environmental variables that best matched tintinnid distributions were temperature and salinity, while the best match for aloricate ciliate distributions was temperature. Therefore, temperature might play a key role in ciliate distribution. These results provide basic data on the response of planktonic ciliate community to hydrographic variations, and implicated potential response of microzooplankton to Pacification as rapid warming progresses in the Pacific Arctic Region.